2012
DOI: 10.4067/s0717-95022012000100055
|View full text |Cite
|
Sign up to set email alerts
|

4NQO Carcinogenesis: A Model of Oral Squamous Cell Carcinoma

Abstract: SUMMARY:The experimental oral carcinogenesis induced by the chemical 4-nitroquinoline 1-oxide (4NQO) is one of the most frequent in the study of squamous cell carcinoma of the oral cavity (CCEC). The clear advantage is that the model is very similar to the physiological process of malignancy. The model has clear benefits by and is suitable for applications in therapeutic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…All carcinogenesis evolves from initial cell injury to the formation of a malignant neoplasm (Hanahan, Weinberg, 2011). Histologically, the lesion passes from reactive epithelial changes (such as hyperkeratosis, hyperplasia and acanthosis) or pre-neoplastic changes (including mild, moderate and severe dysplasia) prior to the establishment of an invasive carcinoma (Neville et al, 2009;Rivera, 2012). In a case-control study, Minhas et al (2021) have reported that cytological changes were observed not only in neoplastic epithelial cells but the nonneoplastic epithelial cells are also affected, resulting in cytopathological atypical changes in patients receiving concomitant chemoradiotherapy (CCRT) as a treatment for oral squamous cell carcinoma (OSCC), Nuclear atypia features were higher on the 17th day and end of treatment; whereas, epithelial atypia was mainly observed on the 17th day of CCRT (40 %).…”
Section: Discussionmentioning
confidence: 99%
“…All carcinogenesis evolves from initial cell injury to the formation of a malignant neoplasm (Hanahan, Weinberg, 2011). Histologically, the lesion passes from reactive epithelial changes (such as hyperkeratosis, hyperplasia and acanthosis) or pre-neoplastic changes (including mild, moderate and severe dysplasia) prior to the establishment of an invasive carcinoma (Neville et al, 2009;Rivera, 2012). In a case-control study, Minhas et al (2021) have reported that cytological changes were observed not only in neoplastic epithelial cells but the nonneoplastic epithelial cells are also affected, resulting in cytopathological atypical changes in patients receiving concomitant chemoradiotherapy (CCRT) as a treatment for oral squamous cell carcinoma (OSCC), Nuclear atypia features were higher on the 17th day and end of treatment; whereas, epithelial atypia was mainly observed on the 17th day of CCRT (40 %).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of a mouse model was due to its ability to form all phases of OSCC (dysplasia, carcinoma in situ, and OSSC with its different grades) and its sensitivity to demonstrating the effects of anti-cancer treatments 39 , 40 . Carcinogenesis is a long multistage process in which invasion was induced after several months but it is proven by some studies that it was hard to induce OSCC with other chemicals 41 43 . Punch biopsies confirmed the formation of different stages of OSCC 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used model of induced experimental oral (tongue) carcinogenesis that may fulfill our requirement is the usage of 4-nitroquinoline-1-oxide or 4NQO (14,15). 4NQO is a synthetic water soluble carcinogen, causes several systemic and molecular damages by promoting DNA adduct formation and intracellular oxidative stress (16).…”
Section: Introductionmentioning
confidence: 99%